Distribuição espacial da resistência do solo vista sob o prisma da fragilidade ambiental para a Área de Proteção Ambiental (APA) de Botucatu - Yoshida, Fernando de Alvarenga (Universidade Federal de São Carlos, 2015)
This study, conducted in the limits of EPA of Botucatu, sought by the spatial distribution of soil strength, prepare an environmental fragility index of soil resistance and using methodologies such as the analysis of environmental fragility, geostatistics and multi-criteria decision analysis generate a environmental fragility map of the study object. The sample area was divided into 78 quadrants where data were collected on the soil resistance with an impact penetrometer, slope, soil types and land use and vegetation cover. It has been prepared an environmental fragility index for soil strength and weaknesses and maps were generated for each parameter and raised by map algebra in a multi-criteria decision analysis, the preparation of the environmental fragility map. The results can be noted that the slope, the lowest average of soil resistance were found in the higher slope (2,38 MPa - 20-40% and 2,92 MPa - greater than 40%) and this group showed significant differences compared to other classes of minor steepness (6.44 MPa to 6%, 7.11 MPa 6 to 12 MPa and 4.85% from 12 to 20%) at a depth of 0 to 20cm. There were significant differences between the different types of land use and vegetation cover. Sugarcane (9,35 MPa) and grazing (9,05 MPa) had the highest average resistance, differing from citrus (6.23 MPa) that differed from perennial crops such as eucalyptus forests (5,28 MPa), the coffee (3,58 MPa) and native forests (2,33 MPa) that formed the last group of least resistance in the layer 0-20 cm soil. In the spatial distribution of soil resistance, ordinary kriging in the exponential semivariogram model proved the most efficient method, given the parameters of the cross validation compared with gausian and spherical models. The multi-criteria decision analysis, through map algebra, generated the final product of this study, the map of environmental fragility to the EPA of Botucatu which showed that 32.43% of the total sample area are within lower fragility environmental classes and 67.57% of the total sample area are averaged fragility classes to very high fragility.
Keywords: Solos; Solos - Compactação; Álgebra de mapas; Diagnóstico ambiental; Geoestatística; Soil compaction; Environmental assessment; Geostatistics; Multi-criteria decision analysis; Map algebra; CIENCIAS EXATAS E DA TERRA